CAR TUNING IN ADVANCED DESIGN PROCESS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In the advanced design process, car tuning means improving or changing a car's exterior, interior, mechanical systems, or technological capabilities. Tuning is often done to improve the appearance, power or performance of a vehicle. This process is mainly aimed at making the car more modern, powerful and aesthetically attractive.